In-vitro Antioxidant and Anticancer Studies of Date Palm (Phoenix dactylifera L.) Seed Extract and Its Oil on Seven Cell Lines with Molecular Docking Study Targeting PI3K and EGFR Inhibition - Amina El-Shaibany; Gehad M. Elnagar; Ali E. Raslan; Ahmed S. Abdelkhalek; Naif A. Al-Gabri; Mahmoud M. Elaasser; Nesreen M. I. M. Elkomy (Zagazig Journal of Pharmaceutical Sciences, 2024)
Introduction: Natural products and neutraceuticals are considered important sources of anticancer medicines. The study was conducted to investigate the in-vitro antioxidant and anticancer activities of date palm (Phoenix dactylifera L.) seed extract (DPSE) and its oil (Oi-Y) against seven cancer cell lines with new insights for the proposed anticancer mechanism of action via molecular docking study for the major active constituents with inhibitory effect on phosphatidylinositol-3-kinase (PI3K) and antagonistic action of epidermal growth factor receptor (EGFR). Materials and methods: The antioxidant assay was conducted using DPPH radical scavenging activity. The anticancer activities were investigated using a variety of cell lines, including HCT-116 (colon carcinoma), HepG-2 (hepatocellular carcinoma), PC-3 (prostate cancer), A-549 (lung adenocarcinoma), HeLa (cervical cancer), HEP-2 (human larynx epithelial carcinoma), and MCF-7 (breast carcinoma). They were quantitatively determined for their in-vitro anti-neoplastic activities using a colorimetric technique. The IC50 values was computed by using optical density. Positive control was performed using doxorubicin. Results: DPSE and Oi-Y showed strong antioxidant activity compared to ascorbic acid. The oil was found to have strong cytotoxic effects on the tested cell lines than DPSE. The HepG-2 cell line was the most susceptible cell line with an IC50 value of 11.18 µg/ml. Molecular docking results showed that oleuropein, luteolin-7-O-glucoside, apigenin-7-O-glucoside, and chromone 1 interestingly binds with high scores with the selected PI3K and EGFR target sites. Conclusions: Our experiment showed that date palm seed extract and its oil could considerably a novel source of anticancer agents.